Identification of Chemical Compounds in Black Garlic Extract and Effect on Inhibiting Xanthine Oxidase Enzyme - Afifah, Mahrunisa Nur; Herdyastuti, Nuniek (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Xanthine oxidase is an enzyme involved in the catalysis of the oxidation reaction that converts hypoxanthine into xanthine and subsequently into uric acid. Elevated uric acid levels can pose various health risks. Gout treatment can be achieved by inhibiting the activity of the xanthine oxidase enzyme using black garlic. This study aims to identify the chemical compounds in black garlic methanol extract, assess the inhibitory effect of this extract on the xanthine oxidase enzyme using in silico methods, and determine the type of inhibition based on enzyme kinetics. The in silico analysis was conducted to evaluate the binding affinity of flavonoid compounds in black garlic extract with xanthine oxidase. The in vitro analysis tested the inhibition of the xanthine oxidase enzyme by black garlic using the UV-Vis spectrophotometry method at a wavelength of 291.7 nm, based on a decrease in uric acid concentration as an indicator of reduced enzyme activity. The type of inhibition mechanism was determined through enzyme kinetics using the Michaelis-Menten equation, which was transformed into the Lineweaver-Burk equation in a double reciprocal form. Black garlic methanol extract contains 133 chemical compounds, including 22 flavonoid compounds that are thought to inhibit xanthine oxidase. According to in silico studies, quercetin-3-O-malonylglucoside exhibits the lowest binding affinity (-9.2 kcal/mol) with the xanthine oxidase enzyme compared to the xanthine substrate (-5.2 kcal/mol) and allopurinol (-5.3 kcal/mol). Inhibition of the xanthine oxidase enzyme by black garlic demonstrated the highest inhibition of 76.352% at a concentration of 10 ppm of black garlic extract. The inhibition type of the xanthine oxidase enzyme by black garlic methanol extract showed a competitive inhibition mechanism, evidenced by an increase in the KM value from 0.014 to 0.134 without a significant change in the Vmax value. Thus, it can be concluded that black garlic extract has the potential to be a natural inhibitor of the enzyme xanthine oxidase that can be used to treat gout or hyperuricemia.